DIELECTRIC-PROPERTIES AND MICROSTRUCTURAL BEHAVIOR OF B-SITE CALCIUM-DOPED BARIUM-TITANATE CERAMICS - PARK, JG; OH, TS; KIM, YH (CHAPMAN HALL LTD, 1992)
Dielectric properties and microstructural behaviour of Ba1-xSrxTi1-yCayO3-y ceramics, where strontium and calcium were doped on the barium and titanium sites, respectively, within the range 0 less-than-or-equal-to x less-than-or-equal-to 0.24 and 0 less-than-equal-to y less-than-or-equal-to 0.05, were investigated. Calcium addition decreased the tetragonality, c/a, increased the unit cell volume, and lowered the Curie temperature, which were all attributed to the occupancy of Ca2+ ions on titanium sites. When sintered at a low oxygen partial pressure of 10(-9) MPa, a resistivity higher than 10(11) OMEGA cm was maintained for the formulations containing B-site calcium substitution more than 0.5 mol %. With increasing the amount of calcium addition, the Curie peak was depressed and completely broadened for the compositions with calcium addition more than 3 mol %, where the average grain size was smaller than 1 mum. Co-firing with nickel electrodes in a reducing atmosphere also depressed the Curie peak and inhibited the grain growth due to the diffusion of nickel into the dielectrics.
Keywords: BATIO3